Experience in Bedside Placement, Clinical Validity, and Cost‐Efficacy of a Self‐Propelled Nasojejunal Feeding Tube. (24th July 2015) - Puiggròs, Carolina; Molinos, Rosa; Ortiz, M. Dolors; Ribas, Montserrat; Romero, Carlos; Vázquez, Concepcion; Segurola, Hegoi; Burgos, Rosa
Abstract : Background: The procedures needed to insert nasojejunal tubes (NJTs) are often invasive or uncomfortable for the patient and require hospital resources. The objectives of this study were to describe our experience in inserting a self‐propelling NJT with distal pigtail end and evaluate clinical validity and cost efficacy of this enteral nutrition (EN) approach compared with parenteral nutrition (PN). Materials and Methods: Prospective study from July 2009 to December 2010, including hospitalized noncritical patients who required short‐term jejunal EN. The tubes were inserted at bedside, using intravenous erythromycin as a prokinetic drug. Positioning was considered correct when the distal end was beyond the ligament of Treitz. Migration failure was considered when the tube was not positioned into the jejunum within 48 hours postinsertion. Results: Fifty‐six insertions were recorded in 47 patients, most frequently in severe acute pancreatitis (69.6%). The migration rates at 18 and 48 hours postinsertion were 73.2% and 82.1%, respectively. There was migration failure in 8.9% of cases, and 8.9% were classified null (the tube was no longer in the gastrointestinal tract at 18 hours). There were no reported or observed complications. The mean duration of the EN was 12 ± 10.8 days. Five different types of EN formula were used. The total study cost was 53.9% lower compared with using PN in all patients. Conclusions: Our study demonstrated that bedside insertion of a self‐propelling NJT is a safe, cost‐effective, and successful technique for postpyloric enteral feeding in at least 73% of the patients, and only 18% of patients could eventually need other placement techniques. It can avoid the need for more aggressive or expensive placement techniques or even PN if we cannot achieve enteral access.